Use of Serotonergic Drugs in Canada for Gastrointestinal Motility Disorders: Results of a Retrospective Cohort Study. (30th May 2016) - Kidane, Biniam; Manji, Farouq; Lam, Jennifer; Taylor, Brian M.
Abstract : Background. Surgery for GI dysmotility is limited to those with severe refractory disease. Though effective, use of serotonergic promotility drugs has been restricted in Canada due to adverse events. We aimed to investigate utilization of promotility serotonergic drugs in patients under consideration for surgical management. Methods. A retrospective cohort study was conducted using prospectively collected data. The study population included consecutive patients referred to a motility clinic for consideration of bowel resection at a Canadian tertiary hospital (1996–2011). Univariable tests and multivariable logistic regression analyses were used to assess predictors of serotonergic drug use. Results. Of 128 patients, the majority (n = 98, 76.6%) had constipation-dominant symptoms. Only 25% (n = 32 ) had tried serotonergic promotility drugs. There was no association between use of these drugs and severity of constipation nor was there an association between serotonergic drug use and presence of diffuse dysmotility (allp > 0.05 ). The majority of patients (n = 97, 75.8%) underwent some type of surgical resection, which was associated with considerable morbidity (n = 13, 13.4%). Conclusions. Surgical management of GI dysmotility results in serious morbidity. Serotonergic promotility drugs may allow patients to avoid surgery but disease severity does not predict use of these drugs.